'Thou shalt not tempt the Lord': Byron's Miltonic Manfred and Wordsworthian Temptations. Issue 1 (June 2019) - Weißenfels, Dennis
Abstract : This article explores Byron's sophisticated use of the Christian temptation narrative in his metaphysical drama Manfred . Adapting the mythotype to suit his own agenda and integrating it into the structure of his play, Byron's plot is filtered by his readings of both Milton and Wordsworth. Byron identifies his own protagonist with Milton's Satan, whilst simultaneously taking apart that very role as he juxtaposes it with the equally suitable role of the Son. Yet both possible frames of reference are revealed to be unsuitable for Manfred's solipsistic outlook. Instead, he manages to utilise both Satan's and Christ's rhetoric to point out the shortcomings of external mechanisms of salvation and damnation, while at the same time he leaves ultimate judgements on his own part open to doubt.